Modelling of high pressure CO2 absorption using PZ+AMP blended solution in a packed absorption column - Hairul, N.A.H. (Elsevier B.V., 2016)
A rate-based steady-state model for CO2 absorption into a PZ+AMP blended solution is presented by taking into account the column hydraulics, mass transfer resistances and chemical reactions. The simulation results were compared with the experimental results of CO2 absorption by a PZ+AMP blended solution in a packed absorption column at low and high CO2 partial pressure conditions. The model predicts CO2 concentration, amine concentration, the chemical enhancement factor, and liquid temperature profiles along the column. The model was in good agreement to predict the CO2 concentration profiles along the column at low CO2 partial pressure. However, it was found that the model needs to be corrected by introducing a correction factor for overall volumetric mass transfer coefficient (Kgae) for the simulation of CO2 concentration profiles along the column at high CO2 partial pressure conditions in the range of 404-1616 kPa. Â© 2016 Elsevier B.V. All rights reserved.